Pola Tindak Tutur Ilokusi Dosen dalam Umpan Balik Presentasi Mahasiswa: Kajian Pragmatik pada Program Studi Pendidikan Bahasa dan Sastra Indonesia - Septi Kartika Sari; Sujarno (Adjektiva: Educational Languages and Literature Studies, 2026)
This study aims to describe the types of lecturers’ illocutionary speech acts and identify the dominant speech act patterns in feedback during student presentations in the Indonesian Language and Literature Education Study Program. The research employed a qualitative approach with a descriptive-interpretative design. The data consisted of lecturers’ spoken utterances during feedback sessions, collected through non-participant observation, audio recording, verbatim transcription, and documentation. Data analysis was conducted through utterance segmentation, illocutionary coding based on Searle’s classification, frequency calculation, and speech act pattern identification. The findings revealed five types of illocutionary speech acts used by lecturers, namely directive, representative, declarative, expressive, and commissive acts. Directive speech acts were the most dominant type, accounting for 44.44%, followed by representative acts (29.63%), declarative acts (14.81%), expressive acts (7.41%), and commissive acts (3.70%). The dominance of directive speech acts indicates that lecturers’ feedback was primarily aimed at encouraging student participation, responses, and reflective thinking processes. In addition, two main sequential patterns were identified, namely the expressive–directive pattern characterized as appreciative-corrective and the representative–directive–expressive pattern characterized as clarification-reinforcement. These findings demonstrate that lecturers’ feedback functions not only as academic evaluation but also as a pedagogical strategy that fosters communicative, dialogic, and reflective classroom interaction.